Nutritional Composition of Dikiri Coconut - K. D. P. P. Gunathilake; Chamila Thilakahewa; A. A. N. Kumara (International Coconut Community, 2009)
Dikiri, an abnormal type of coconut found mainly in the southern part of Sri Lanka, was analyzed for its proximate composition, dietary fiber, minerals, vitamin C and fatty acid profile. Pectin was isolated and characterized (moisture, ash, acetyl value, methoxyl value, equivalent value) from dikiri coconut. Dikiri coconut contains 38.91± 0.9%, 2.95 ± 0.2%, 58.21± 3.6%, 17.62 ± 0.2%, 6.63 ± 0.3% and14.59% dry matter, ash, crude fat, crude fibre and carbohydrate respectively. The main dietary fiber components of Dikiri coconut were pectin and hemicellulose while that of normal coconut was cellulose. Lignin content was significantly lower in the kernel of dikiri coconut(3.98±0.9) than normal coconut kernel(6.14±0.7%). Equivalent weight, methoxyl value, moisture, ash and acetyl value of dikiri pectin were 1052.7 ± 11.08, 8.72 ± 0.25, 85.8 ±1.65, 0.8 ± 0.04 and 0.09 ± 0.01 respectively. The main mineral found in dikiri was potassium. Vitamin C content of dikiri coconut was 2.32 mg/100g. The fatty acids composition of dikiri was similar to normal coconut and saturated fatty acids constituted nearly 90% of total fatty acids and lauric acid is the main fatty acid followed by myristic acid.